2001
DOI: 10.1111/j.1748-7692.2001.tb01304.x
|View full text |Cite
|
Sign up to set email alerts
|

DIET OF RINGED SEALS (PHOCA HISPIDA) ON THE EAST AND WEST SIDES OF THE NORTH WATER POLYNYA, NORTHERN BAFFIN BAY

Abstract: In conjunction with the International North Water Polynya Study (NOW) in northern Baffin Bay, we examined the diets of ringed seals (Phoca hispida)1 on the west (Grise Fiord, Nunavut) and east (Qaanaaq, Greenland) sides of the polynya, using conventional stomach content analysis, as well as inferences from stable isotope ratios in seal muscle. Between May and July 1998, stomach and muscle tissue samples were collected from 99 ringed seals taken near Grise Fiord and 100 taken near Qaanaaq. The amphipod Themisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 46 publications
10
77
0
Order By: Relevance
“…Age estimates from ringed seals collected in Ulukhaktok were provided by counting growth layer groups in the dentine layers of canine teeth. Stewart et al (1996) indicated that this method underestimates ages of older seals (>10 years of age), but this will have no effect on our results, as all seals have been grouped into separate age classes based on age of sexual maturity: adults (≥6 years of age) and subadults (1-5 years of age; McLaren 1958; Holst and Stirling 2002).…”
Section: Sample Collection and Preparationmentioning
confidence: 90%
See 1 more Smart Citation
“…Age estimates from ringed seals collected in Ulukhaktok were provided by counting growth layer groups in the dentine layers of canine teeth. Stewart et al (1996) indicated that this method underestimates ages of older seals (>10 years of age), but this will have no effect on our results, as all seals have been grouped into separate age classes based on age of sexual maturity: adults (≥6 years of age) and subadults (1-5 years of age; McLaren 1958; Holst and Stirling 2002).…”
Section: Sample Collection and Preparationmentioning
confidence: 90%
“…The life history of ringed seals has been strongly shaped by sea ice dynamics (Smith and Hammill 1981), as stable land-fast ice is their preferred breeding habitat over pack ice (Smith and Stirling 1975). Ringed seals are trophic omnivorous consumers (Weslawski et al 1994;Dehn et al 2007;Labansen et al 2007;Thiemann et al 2007) that have been reported to undergo an ontogenetic shift in diet from invertebrates to fish (Bradstreet and Cross 1982;Holst et al 2001;Young et al 2010). Ringed seals consume a wide variety of prey species, from herbivorous and carnivorous invertebrates such as mysid, euphausiid, amphipod, and decapod species to fish such as Arctic cod (Boreogadus saida), capelin (Mallotus villosus), sand lance (Ammodytes sp.…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been directed, however, to investigating the possible influence of prey densities or availability on selection of breeding habitat (Nazarenko 1967;Siegstad et al 1998;Holst et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…100 ringed seals) and also because seals were sampled from the Canadian Arctic (McLaren 1993), reducing the effect of regional variability. The maturity of ringed seals was estimated after counting annual growth layers in canine teeth as follows: adult ]6 years, juvenile 1Á5 years and pup B1 year (Holst et al 2001). Beluga age was estimated by counting annual growth layers deposited in the dentine of mounted tooth sections (Stewart 2012).…”
Section: Age Maturity and Sex Determinationmentioning
confidence: 99%
“…Many ringed seals show area fidelity, Foraging ecology of ringed seals, beluga whales and narwhals J.K. Matley et al but long-range movement and changes in seasonal distribution occur (e.g., Heide-Jørgensen et al 1992). The diet of ringed seals in the High Arctic is dominated by only a few species, including Arctic cod, pelagic amphipods and mysids (Bradstreet & Cross 1982;Marcin 1994;Holst et al 2001;Labansen et al 2011). The purpose of this study was to improve our understanding of the foraging ecology of ringed seals, belugas and narwhals using SCA and SIA in a multi-approach study.…”
mentioning
confidence: 99%